PENGARUH BERBAGAI BAHAN ALAS KANDANG TERHADAP PENAMPILAN PRODUKSI - Lia Liswulandari; Nita opi ari kustanti (Universitas Islam Balitar, 2018)
This study aims to determine the effect of various cage base materials on broiler production performance. Production performances observed in the study were (feed consumption, body weight gain, and feed conversion). Using 90 broilers from DOC 1 day old from PT. Wonokoyo Jaya Corporindoyang was applied into 3 treatments and 6 replications consisted of 5 broilers. Chicken maintenance is carried out 35 days. The treatments used in the study are as follows: P1 (giving pedestal of candan gsekam padi), P2 (giving treatment for wooden shed cage bed), and P3 (giving sand cage bed). This data is a complete randomized design and then analyzed using variance analysis (ANOVA) and if significantly different then continued with multiple further tests (Duncan). The conclusion of this study showed that giving broiler cage material was not significantly different (P> 0.05) on broiler production performance which included feed consumption, body weight gain, and feed conversion.